Optimization of biocomposite materials for outer shell of buildings (2019)
The subject of the article is a bio-composite material which will serve as the outer shell for buildings. It deals with the testing and optimization of bio-composite laminate. Conventional constructions materials, such are steel and plastic are currently used for buldings envelopes. Bio-composites may be used as a suitable alternative material. They are made by nature fibers and matrix. Bio-composites will have great potential in the future in the construction industry as the outer envelope of buildings. The main intention of this article is to analyze the impact of UV radiation and humidity on bio-composites and creation a bio-composite panel for using in building envelope with inclusion of wider use of these types of materials in the future.